2016
DOI: 10.3892/ijo.2016.3390
|View full text |Cite
|
Sign up to set email alerts
|

The milk-derived hexapeptide PGPIPN inhibits the invasion and migration of human ovarian cancer cells by regulating the expression of MTA1 and NM23H1 genes

Abstract: Abstract. Some bioactive peptides derived from natural resources or synthesized by rational design have been proved to have very good anticancer effect. We studied the inhibition of PGPIPN, a hexapeptide derived from bovine β-casein, on the invasion and metastasis of human ovarian cancer cells in vitro and its molecular mechanism. The human ovarian cancer cells studied include the cell line SKOV 3 as well as the primary ovarian cancer cells from ovarian tumor tissues of 37 patients at initial debulking surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Recently, a peptide (PGPIPN), isolated from a bovine b-casein hydrolysate and previously reported to have immunomodulatory activity (Migliore-Samour et al, 1989), was studied for its anti-cancer activity. This study found that the peptide inhibited the invasion and migration of ovarian cancer cells in culture and also inhibited in vitro colony formation in these cells (Zhao et al, 2016). A blood-derived compound, valorphin, released by proteolytic cleavage of haemoglobin, has also been reported to have anti-cancer effects.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Recently, a peptide (PGPIPN), isolated from a bovine b-casein hydrolysate and previously reported to have immunomodulatory activity (Migliore-Samour et al, 1989), was studied for its anti-cancer activity. This study found that the peptide inhibited the invasion and migration of ovarian cancer cells in culture and also inhibited in vitro colony formation in these cells (Zhao et al, 2016). A blood-derived compound, valorphin, released by proteolytic cleavage of haemoglobin, has also been reported to have anti-cancer effects.…”
Section: Discussionmentioning
confidence: 82%
“…It was reported that several of the collagen hydrolysate fractions showed a significant antiproliferative activity and increased caspase-3 activity in cells (Castro et al, 2009). This study found that the peptide inhibited the invasion and migration of ovarian cancer cells in culture and also inhibited in vitro colony formation in these cells (Zhao et al, 2016). Recently, a peptide (PGPIPN), isolated from a bovine b-casein hydrolysate and previously reported to have immunomodulatory activity (Migliore-Samour et al, 1989), was studied for its anti-cancer activity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…PGPIPN from bovine milk protein has demonstrated various effects including immunoregulation and anti-cancer [ 15 , 16 ]. The milk peptides are safe to consume orally for healthy volunteers and no clinically significant side effects are reported [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cancer and normal cells vary greatly in cell membrane proteins and signaling pathways. Our previous studies indicated that PGPIPN could induce apoptosis of ovarian cancer cells [ 15 , 16 ]. This experiment showed that CHOP and Caspase-3 levels were very low in steatosis hepatocyte model established with hepatocellular carcinoma cell HepG2.…”
Section: Discussionmentioning
confidence: 99%